The School of Music from Real Sociedad Económica de Amigos del País de Santiago de Compostela (1877-1953) (Revista Argentina de Musicología, 2016)
The institutions to call Sociedades Económicas were cultural centers during the second half of the century XVIII, serving these for the promotion of it education Spanish. In Santiago of Compostela was implemented, in 1784, a Real Sociedad Económica de Amigos del País, which developed a significant instructional work with the creation and promotion of different schools for the training of its people. One of these was the music, which was established in 1877 and was linked to the Sociedad Económica until 1953, year that it reached the title of Regional Conservatory in Santiago of Compostela, independent institutionally of the Real Sociedad. This research, which was addressed from a historical perspective and descriptive, it has grounded in the records of the Real Sociedad Económica de Amigos del País, currently preserved in the archive of the city of culture, in newspapers of the time, as well as in Galician historical publications. The bibliographic investigation carried out for the development of this paper notes the paucity of studies and stories about the school of music of this institution, which over the years was neglected by researchers, however, it was a significant part in the history of Galician music during its seventy-six years of existence.
Keywords: Real Sociedad Económica de Amigos del País; School of Music; 19th - 20th; instruction